O projeto de pesquisa e sua relação com a descoberta científica - de la Lama Zubirán, Paula (2022)
This article explains why scientists should have a true existential commitment to the problem to be investigated in order to delve into its secrets and solve them. That the written formulation of a research project, eventually, allows generating a scientific discovery. That the project to continue must be submitted to the appreciation of a thesis advisor if he wishes to be accepted into a postgraduate degree, or to a collegiate if he wishes to use the institution's resources; and it will finally allow to appreciate how the stages of said project are linked to each other and the importance of solving each one satisfactorily.